Terra incognita—cerebellar contributions to neuropsychiatric and cognitive dysfunction in behavioral variant frontotemporal dementia - Tan, Rachel H.; Devenney, Emma; Kiernan, Matthew C.; Halliday, Glenda M.; Hodges, John R.; Hornberger, Michael (Frontiers in Aging Neuroscience, 2015)
Although converging evidence has positioned the human cerebellum as an important relay for intact cognitive and neuropsychiatric processing, changes in this large structure remain mostly overlooked in behavioural variant frontotemporal dementia (bvFTD), a disease which is characterized by cognitive and neuropsychiatric deficits. The present study assessed whether degeneration in specific cerebellar subregions associate with indices of cognition and neuropsychiatric performance in bvFTD. Our results demonstrate a relationship between cognitive and neuropsychiatric decline across various domains of memory, language, emotion, executive, visuospatial function and motivation and the degree of grey matter degeneration in cerebellar lobules V-VII. Most notably, bilateral cerebellar lobule VII and the posterior vermis emerged as distinct for memory processes, the right cerebellar hemisphere underpinned emotion, and the posterior vermis was highlighted in language dysfunction in bvFTD. Based on cortico-cerebellar connectivity maps, these findings in the cerebellum are consistent with the neural connections with the cortices involved in these domains in patients with bvFTD. Overall, the present study underscores the significance of cortical-cerebellar networks associated with cognition and neuropsychiatric dysfunction in bvFTD.